A kinetic study of fusion burn waves in compressed deuterium–tritium and proton–boron plasmas - Lavell, Michael J.; Kish, Ayden J.; Sexton, Andrew T.; Evans, Eugene S.; Mohammad, Ibrahim; Gomez-Ramirez, Sara; Scullin, William; Borscz, Marcus; Pikuz, Sergey; Mehlhorn, Thomas A.; Tabak, Max; Ainsworth, Greg; et al. (Frontiers in Physics, 2024)
We present particle-in-cell simulations with Monte Carlo collisions of fusion burn waves in compressed deuterium–tritium and proton–boron plasmas. We study the energy balance in the one-dimensional expansion of a hot-spot by simulating Coulomb collisions, fusion reactions, and bremsstrahlung emission with a Monte Carlo model and inverse bremsstrahlung absorption using a new PIC model. This allows us to self-consistently capture the alpha particle heating and radiative losses in the expanding hot-spot and surrounding cold fuel. After verifying our model in a code-to-code comparison with both kinetic and fluid codes for the case of a deuterium–tritium hot-spot, we simulate the expansion of a proton–boron hot-spot initialized at 200 keV and 1,000 g/cm3. Our model predicts that energy radiated by the hot-spot is recaptured by the surrounding high-density opaque fuel reducing the expansion work done by the propagating burn wave. As a result, we find the net fusion energy produced over the course of 20∼ps is twice the initial hot-spot energy independent of whether radiation physics is included.